Model priprave in izvedbe projektov digitalizacije - primer osrednjeslovenske regije - Frković, Anja (Knjižnica, 2012)
The Ljubljana City Library has been cooperating in the KAMRA project since its very beginning. KAMRA is a Slovenian cross regional portal joining central regional public libraries as defined in the regulations on Central Regional Libraries. It was established in order to digitise local studies collections , to promote the collections and the cooperation among different local institutions. The paper outlines the problems related to the collection and selection of relevant library materials to be incorporatedin the KAMRA portal. It deals with copyright regulations for web publications and outlines the importance of obtaining the copyright permission for the use of library materials which were digitised after they were exhibited in the physical form. The Ljubljana City Library often decides to digitise hard copies of important items of local studies collection exhibited in the Slovanska Library - a branch library of the Ljubljana City Library. For the needs of the KAMRA portal the Ljubljana City Library created the project My Street (Moja ulica)joining public libraries in the central Slovenian region. They research the history, development, culture and life of people living in particular streets and areas and publish their stories on the KAMRA portal. The City Library of Ljubljana tries to cooperate with other regional cultural institutions, associations and individuals thus enabling access to local information sources which would otherwise be hard to access. The paper also deals with the mission and concepts of the Digital Library of Slovenia (dLib.si) and the KAMRA portal as well as with the digitisation of local studies. At the end it points to the problem of lack of financial means for digitisation projects.
Keywords: splošne knjižnice; Mestna knjižnica Ljubljana; digitalizacija; digitization; spletni portali; portal KAMRA; projekti; Digital Library of Slovenia; Digitalna knjižnica Slovenije